Peel Off Face Masker from Coffee Grounds-Chitosan - Agung R Gintu; Glory P. V. Fanggidae; Christian H. J de Fretes; Dhanang Puspita (Future Science, 2023)
Face skin is one of the sensitive skin covering the human body. For the women, face skin was an important part of care. But sometimes skin care products cause bad side effects to the skin and the body's health. Because of this, Pharmaceutical and Cosmetics research was initiated to produce the advanced materials to be applied in Cosmetics formulations. In this study, the processing of Coffee grounds became a suitable compound for skin care. The Coffee grounds were activated to increase its performance. The Coffee grounds were mixed with the Chitosan to make the Biofilm and then applied as a peel-off face, Masker. The results of antibacterial, antioxidant, and SPF protection in all treatments showed a “strong” to “very strong” activity range. Based on these results concluded that this face masker was recommended for production as a skin care product.